STRUCTURE-FUNCTION OF THE TUMOR SUPPRESSOR BRCA1 - Serena L. Clark; Ana M. Rodriguez; Russell R. Snyder; Gary D.V. Hankins; Darren Boehning (Computational and Structural Biotechnology Journal, 2012)
BRCA1, a multi-domain protein, is mutated in a large percentage of hereditary breast and ovarian cancers. BRCA1 is most often mutated in three domains or regions: the N-terminal RING domain, exons 11–13, and the BRCT domain. The BRCA1 RING domain is responsible for the E3 ubiquitin ligase activity of BRCA1 and mediates interactions between BRCA1 and other proteins. BRCA1 ubiquitinates several proteins with various functions. The BRCA1 BRCT domain binds to phosphoproteins with specific sequences recognized by both BRCA1 and ATM/ATR kinases. Structural studies of the RING and BRCT domains have revealed the molecular basis by which cancer causing mutations impact the functions of BRCA1. While no structural data is available for the amino acids encoded by exons 11–13, multiple binding sites and functional domains exist in this region. Many mutations in exons 11–13 have deleterious effects on the function of these domains. In this mini-review, we examine the structure-function relationships of the BRCA1 protein and the relevance to cancer progression.